A conceptual analysis of group privacy in the virtual environment. (13th August 2009) - Surendra, Nanda; Peace, A. Graham
While individual privacy has been the subject of considerable research in both the face-to-face and virtual environments, the idea of 'group privacy' has received less attention. Proponents advocate the idea of group privacy on the following two principles: 1) Group privacy should protect the need of people to come together to exchange information and share feelings. In this process, people reveal themselves to one another and rely on the others in the group to keep this information within the group. 2) The combination of information disseminated about a group and the realisation that a certain individual is a member of that group can potentially violate that individual's privacy. In the virtual environment, group privacy may be as important as individual privacy, given the popularity and pervasiveness of discussion forums, e-mail listservs and 'social networking' websites, such as Facebook and MySpace. This paper provides an overview of group privacy, the impact of virtual communities on group privacy and a discussion of potential future research in this important area.